MICROSTRIP ANTENNA ARRAY FOR THE GROUND SEGMENT OF THE UAV CONTROL SYSTEM - Shcherbyna, Olga; Zadorozhny, Oleksandr; Torubara, Rodion (Science-based technologies, 2023)
Antennas used both on UAVs and in their control systems should be low profile and compact. With the increase in data rates and the trend towards miniaturized electronic circuits for wireless digital applications, the antennas required for these applications must be light in weight and size, easy to mount, and have a sufficiently wide bandwidth. These requirements can be met with microstrip antenna arrays. The antenna should be low profile, simple and inexpensive to manufacture, and it should also be easy to mount on surfaces of various shapes. The article discusses the principles of constructing flat linear equidistant in-phase antenna arrays with a static amplitude-phase distribution. Using these principles, a microstrip flat antenna array was built. The results of modeling microstrip antenna array with a dimension of 4x2, the elements of which are folded dipoles, showed the possibility of forming a radiation pattern with such an antenna array with a beamwidth sufficient for the intended purposes in terms of the half-power radiation level. When placing the antenna to work with vertical polarization, the beamwidth of the radiation pattern in the horizontal plane was 18 degrees, in the vertical plane was 37,5 degrees. In this case, the level of side lobes does not exceed -10 dB. The gain of the microstrip antenna array at the central frequency of operation reaches 10,17 dBi. Good matching of a standard coaxial power line, the resistance of which is 50 ohms, with a microband antenna array has been achieved. The value of the voltage standing wave ratio remains less than 2 in the 250 MHz frequency band. At the center frequency of 5,8 GHz, its value is 1,25.